Electrocatalytic oxygen reduction by a Co/Co3O4@N-doped carbon composite material derived from the pyrolysis of ZIF-67/poplar flowers. Issue 5 (11th January 2021) - Wu, Yanling; Wang, Yanmin; Xiao, Zuoxu; Li, Miantuo; Ding, Yongling; Qi, Mei-li
Abstract : Co/Co3 O4 @NC catalyst for the ORR with a low cost and highly stable performance is developed through the pyrolysis of an easy physical mixture containing ZIF-67 as the precursor and poplar flowers as the carbon source. Abstract : Catalysts used for the oxygen reduction reaction (ORR) are crucial to fuel cells. However, the development of novel catalysts possessing high activity at a low cost is very challenging. Recently, extensive research has indicated that nitrogen-doped carbon materials, which include nonprecious metals as well as metal-based oxides, can be used as excellent candidates for the ORR. Here, Co/Co3 O4 @N-doped carbon (NC) with a low cost and highly stable performance is utilized as an ORR electrocatalyst through the pyrolysis of an easily prepared physical mixture containing a cobalt-based zeolite imidazolate framework (ZIF-67 precursor) and biomass materials from poplar flowers. Compared with the pure ZIF-derived counterpart (Co@NC) and PL-bio-C, the as-synthesized electrocatalysts show significantly enhanced ORR activities. The essential roles of doped atoms (ZIF-67 precursor) in improving the ORR activities are discussed. Depending mainly on the formation of Co–Co3 O4 active sites and abundant nitrogen-containing groups, the resulting Co/Co3 O4 @NC catalyst exhibits good electroactivity (onset and half-wave potentials: E onset = 0.94 V and E 1/2 = 0.85 V, respectively, and a small Tafel slope of 90 mV dec −1 ) compared to Co@NC and PL-bio-C and follows the 4-electron pathway with good stability and methanol resistance. The results of this study provide a reference for exploring cobalt-based N-doped biomass carbon for energy conversion and storage applications.